Self-initiated programming activity as a factor in developing students’ skills in school education: Preliminary research findings - Maciej (Multidisciplinary Journal of School Education, 2025)
Research objectives (aims) and problem(s): The study aims to examine the impact of secondary school students’ programming activity on the development of specific skills in various areas of school education. It also seeks to identify factors that influence students’ engagement in programming and the motivations behind their participation.